Reconstruction Of Thumb By Distraction - A Case Report - Dr. P.K. Sharma; Dr. K.K. Verma; Dr. O.P. Sharma; Dr. A. Malhotra (Indian Journal of Plastic Surgery)
A simple, excellent, practical & effective method of Reconstruction of thumb is described in this distraction technique. Reconstructed thumb is of near normal, colour, texture, sensation, stability, aesthetics, and function wise.